The combination of UASB and ozone technology in the treatment of a pectin containing wastewater from the apple juice processing industry - Van Schalkwyk, Nico (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc )--Stellenbosch University, 2004.